Towards a new relevance for research libraries - Waaijers, Leo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
The invention of printing in 1455 by Johann Gutenberg and the invention of the World Wide Web in 1991 by Tim Berners-Lee have often been compared when it comes to making knowledge accessible. Both events marked a breakthrough with far-reaching social consequences. The printing press led to the disappearance of monastic libraries and their scriptoriums as sources of knowledge, to make way for university libraries and publishers. The Web is again a revolution in the distribution of knowledge, embraced by the academic community and culminating in the Open Science movement. This editorial is an exploration into the challenges that this development poses for the roles of publishers and libraries.